2021
DOI: 10.1038/s41598-021-89967-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in coagulopathy indices in patients with severe versus non-severe COVID-19: a meta-analysis of 35 studies and 6427 patients

Abstract: Coronavirus disease 2019 (COVID-19) is a highly contagious disease that appeared in China in December 2019 and spread rapidly around the world. Several patients with severe COVID-19 infection can develop a coagulopathy according to the ISTH criteria for disseminated intravascular coagulopathy (DIC) with fulminant activation of coagulation, resulting in widespread microvascular thrombosis and consumption of coagulation factors. We conducted a meta-analysis in order to explore differences in coagulopathy indices… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 67 publications
(49 reference statements)
3
19
0
2
Order By: Relevance
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 66%
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 66%
“…Results of a meta-analysis of 35 studies and 6427 patients demonstrate that a severe COVID-19 infection is associated with higher D-dimer values, lower platelet count, and prolonged PT. This data suggest a possible role of disseminated intravascular coagulation in the pathogenesis of severe COVID-19 infection [103]. A favorable outcome has been reported with the use of heparin in COVID-19 patients, especially in those with markedly high D-dimer levels or with sepsis-induced coagulopathy [104].…”
Section: Covid-19mentioning
confidence: 75%
“…This immune response-triggered thrombosis causes widespread vascular damage, complement-induced thrombosis, systemic microangiopathy, and thromboembolism, that may ultimately lead to multi-organ failure [ 84 , 85 , 86 ]. Additionally, disseminated intravascular coagulopathy (DIC) with fulminant activation of coagulation, also reported in COVID-19 patients, has been shown to induce massive microvascular thrombosis and coagulation factor consumption [ 87 ]. Prolonged activated partial thromboplastin time, elevated D-dimer, and thrombocytopenia are all associated with the development of severe SARS-CoV-2 infection [ 88 ].…”
Section: Hematological Abnormalitymentioning
confidence: 99%
“…D-dimer is a soluble fibrin degradation product used as a marker for evaluating ongoing thrombotic and thrombolytic events such as pulmonary embolism [ 89 ]. D-dimer has been found in increased quantities among COVID-19 patients following the activation of coagulation and fibrinolysis [ 87 ]. As raised D-dimer has been associated with higher in-hospital mortality and increasing COVID-19 severity, it may be a reliable prognostic factor [ 90 ].…”
Section: Hematological Abnormalitymentioning
confidence: 99%